THE INVESTIGATION OF THE STRENGTH REDUCTION FACTOR IN PREDICTING THE SHEAR STRENGTH - Arslan, Guray; Alacali, Sema Noyan; Sagiroglu, Ali (POLISH SOC THEORETICAL & APPLIED MECHANICS, 2015)
Design codes propose to restrict the nominal probability of failure within specific target structural reliability levels using a load factor and a strength reduction factor. In the current ACI318 Code, the strength reduction factor varies from 0.65 to 0.90, and the value considered in predicting the shear strength equals to 0.75. In this study, the change in the strength reduction factor in predicting the shear strength according to ACI318 has been investigated for different coefficients of variation of concrete compressive strength by using the first-order second moment approach, and the strength reduction factor is proposed for the target values of failure probability.
Keywords: reinforced concrete; beam; shear strength; reduction factor; target reliability; REINFORCED-CONCRETE BEAMS; RELIABILITY-BASED DESIGN; WEB REINFORCEMENT; MEMBERS; PERFORMANCE; RESISTANCE; STIRRUPS; SLABS; CODE; Mechanics